Analisisa Persepsi Pengguna Jalan terhadap Dampak Positif dan Negatif Tidak Adanya Median Jalan - Meri Sufina; Nadra Arsyad; Muhammad Hafidz (Universitas Putra Indonesia YPTK Padang, 2020)
Roads are the most common land transportation infrastructure used by the community to carry out daily mobility compared to water and air transportation, so that the volume of vehicles passing through these roads must be able to be supported by pavement on the roads they pass. Median is a path that is located in the middle of the road to divide the road in each direction. The median and its limits must be visible to every driver's eyes both during the day and night and all weather and conditions so that no accident occurs. The purpose of this study was to determine how perceptions of road users on the positive and negative impacts of the absence of a road median on the Sudirman road section. The results of this research can be done by conducting a field survey of road users. After that, the questionnaire was distributed with the number of respondents from the average results for a week of 50 respondents. So that it is obtained from the SPSS statistics. From the research results the validity test of the median variable of road and traffic accidents is declared